The Evaluation of The Parameter Consumer Purchase Intention Towards Green Products Small Medium Enterprises (SMES) During the Covid-19 Pandemic (Case Study of Consumer in Kudus) - Mokhamad Arwani; Mawar Anggraeni; Dina Lusianti; Dhaifina Idznitia A. Naimi (Penerbit Kemala Indonesia, 2021)
A green product is intended to have as little environmental impact as possible, both during its whole life cycle, and after it is no longer in use. Typically, a green product has two primary goals, including waste reduction and resource efficiency maximization. This study aimed to analyse the religiosity of customer purchasing intentions and the theory of knowledge in behaviour planned on a green product. For this study, 150 SMEs of green products SMES in Kudus, Central Java, were taken as sampled. Path analysis using SEM was used in this study. The findings are intended to be able to assess the purchase intention of green products, therefore making a beneficial contribution to spreading awareness of the use of environmentally friendly green products.